THE PROBLEM OF GOOD AND EVIL IN THE PHILOSOPHY OF I.A. ILYIIN - Tsvyk, V.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2017)
The article is devoted to the study and analysis of the ethical concept of IA. Ilyin - the doctrine of the essence and nature of good and evil, the means of opposing evil. In the Russian philosophy of the early twentieth century, the deliverance of the world from evil was declared the main task of mankind. Therefore, in the teachings of the greatest philosophers of this period, attempts to solve the problem of good and evil are often expressed in the desire to identify evil, to find its sources, to show mankind ways and methods of fighting it. In the creative heritage of the outstanding Russian philosopher Ivan Aleksandrovich Il’in, an important place is occupied by the study of the question of the nature of good and evil, the origin of evil, and, most importantly, methods of combating it. Ilyin’s ethic is very relevant, it is of interest to the modern reader precisely because it embodies his personal spiritual and moral experience. The objec-tivity and scientific approach to its study excludes the possibility of its unambiguous evaluation. On the one hand, the present reality and social existence of the first decade of the 21st century. Continues to talk about the human right to use force in the fight against evil. On the other hand, the fact that the path to good lies beyond all violent actions becomes more and more understandable. Outside the non-violent per-spective, the further development of human civilization is impossible, both in terms of interpersonal relations, and at the level of interstate relations and world politics.